Paternal HLA-C and Maternal Killer-Cell Immunoglobulin-Like Receptor Genotypes in the Development of Autism - Gamliel, Moriya; Anderson, Karen L.; Ebstein, Richard P.; Yirmiya, Nurit; Mankuta, David (Frontiers in Pediatrics, 2016)
Killer-cell immunoglobulin-like receptors (KIRs) are a family of cell surface proteins found on natural killer cells, which are components of the innate immune system. KIRs recognize MHC class I proteins, mainly HLA-C and are further divided into two groups: short-tailed 2/3DS activating receptors and long-tailed 2/3DL inhibitory receptors. Based on the Barker Hypothesis, the origins of illness can be traced back to embryonic development in the uterus, and since KIR:HLA interaction figures prominently in the maternal–fetal interface, we investigated whether specific KIR:HLA combinations may be found in autism spectrum disorders (ASD) children compared with their healthy parents. This study enrolled 49 ASD children from different Israeli families, and their healthy parents. Among the parents, a higher frequency of HLA-C2 allotypes was found in the fathers, while its corresponding ligand 2DS1 was found in higher percentage in the maternal group. However, such skewing in KIR:HLA frequencies did not appear in the ASD children. Additionally, analysis of “overall activation” indicated higher activation in maternal than in paternal cohorts.